2019
DOI: 10.1017/prp.2019.9
|View full text |Cite
|
Sign up to set email alerts
|

Racism and the Pinkerton syndrome in Singapore: effects of race on hiring decisions

Abstract: The aim of the study was to examine racism and the Pinkerton syndrome in Singapore. Specifically, the study examined the effects of race on hiring decisions in a simulated hiring decision task. Participants were 171 (61% males) Singaporean Chinese undergraduates from a private university in Singapore. They were randomly assigned into one of nine groups and asked to review a resume of a job applicant. The study used a 3 (Academic qualifications: strong, moderate, or weak) × 3 (Race: White, Chinese, or Malay) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Yet, in both societies, attitudes toward the United States may be relatively more favorable than toward Mainland China. For instance, in Singapore, Chew et al (2019) have shown that Singaporean-Chinese participants showed a positive bias toward a fictitious job candidate paired with an European (White) name and recommended a higher salary to the candidate than the one paired with a Chinese name or Malay name. In Hong Kong, studies (Tadmor et al, 2018; Zhang et al, 2020) have revealed that Hong Kong participants displayed implicit and explicit prejudice against Chinese Mainlanders, which is consistent with the increasing contentious relations between Hong Kong and Mainland China.…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…Yet, in both societies, attitudes toward the United States may be relatively more favorable than toward Mainland China. For instance, in Singapore, Chew et al (2019) have shown that Singaporean-Chinese participants showed a positive bias toward a fictitious job candidate paired with an European (White) name and recommended a higher salary to the candidate than the one paired with a Chinese name or Malay name. In Hong Kong, studies (Tadmor et al, 2018; Zhang et al, 2020) have revealed that Hong Kong participants displayed implicit and explicit prejudice against Chinese Mainlanders, which is consistent with the increasing contentious relations between Hong Kong and Mainland China.…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…Second, Singapore actively promotes a culture of tolerance given that it is a multiracial and multi-religious country (Pew Research Center, 2014;Singapore Department of Statistics, 2010). Although there are some evidence of outgroup derogation (Chew, 2018;Chew et al, 2019), tensions and conflicts between the major ethnic and religious groups are relatively low compared to other countries due to the culture of tolerance. This culture is enforced by laws prohibiting outgroup derogation (Penal Code, 1871;Sedition Act, 1948) and supported by a government that endorses diversity (Roets et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…National statistics indicate that Singapore’s minority Malay population is less socio-economically well-off than the rest of the population, across various domains (Brassard, 2020; Mutalib, 2012). While published studies on why these ethnic disparities exist are few, some highlight ethnic discrimination as an important contributor (Chew et al, 2019; Lee, 2004).…”
Section: Overview Of Singapore’s Social and Housing Policy Landscapementioning
confidence: 99%